Leg-orthosis contact force estimation from gait analysis. (June 2020) - Mouzo, F.; Michaud, F.; Lugris, U.; Cuadrado, J.
Highlights: A new method to estimate leg-orthosis contact forces is proposed. It combines motion-force captures with multibody modeling and forward dynamics. At least one force sensor per orthosis is required. Results suggest that active orthoses lead to lower contact forces. Abstract: Spinal cord injured subjects with hip flexion ability may often walk with the help of orthosis and crutches. Typically, the orthotic devices are attached to the legs by means of several braces. Excessive pressure in such contacts may lead to skin wounds and to subsequent loss of adherence to the use of the orthoses. Since contact pressures are related to contact forces, estimation of the leg-orthosis contact forces is relevant to assess the suitability of an orthotic device for a specific subject, or to redesign the braces for pressure reduction. In this paper, a procedure to estimate such contact forces from simple gait analyses is proposed. It consists of building computational multibody models of subject and devices, and running a forward-dynamics analysis of the orthoses in which the captured motion of the subject is prescribed. At least one force/torque sensor per orthosis is required to calibrate the model. In this case, an extensometry-based load cell was used for such purpose. Results showed that, once calibrated, the model was able to reproduce torque sensor measurements for different motions.